The Tribunal of Zaragoza and Crypto-Judaism - D'Abrera, Anna Ysabel (Brepols, 2008)
Since the opening of the Inquisition's archives in Spain in the nineteenth century, historians and anthropologists alike have seized upon the institution and its remarkable archival legacy, and have scrutinized it from a multitude of political, socio-economic, and cultural angles. Perhaps one of the most contentious hypotheses to have recently emerged from the field has been Benzion Netanyahu's proposal that the inquisitors fabricated charges of Judaizing against the Spanish New Christians (Christians of Jewish descent). This book questions Netanyahu's hypothesis by turning to the extant trial records from Aragon's tribunal of Zaragoza, and employing them as a case study. This range of documents provides ample evidence of a true survival of Jewish ritual life and culture among the Aragonese <span class=